Desenvolvimento de bebida probiótica à base de polpa e extrato de amêndoa de cupuaçu (Theobroma grandiflorum) - Moura, Katherine Leslie Ayres (2023)
The global market for functional foods is constantly growing, and one food that has attracted interest is cupuaçu. This tropical fruit has high nutritional value, functional properties, and the potential to add value to food products. In order to evaluate the effect of formulation and fermentation variables in a medium based on cupuaçu pulp and hydro-soluble extract of cupuaçu almond, preliminary tests were conducted with three microorganisms: Saccharomyces boulardii-17 (SB), Lactobacillus rhamnosus LR32 (LR), and Bifidobacterium longum BL04 (BL). In these tests, the fermentation capacity and viability of each microorganism were analyzed. The kinetics of cell growth, reducing and total sugars (RS and TS), pH, and total titratable acidity (TTA) were observed. In the fermentation kinetics of the prototypes, the assays with SB and LR showed the highest total cell growth counts (TCGC), with an increase of 3.1 Log CFU/mL for both microorganisms. Additionally, these assays also exhibited higher consumption of total sugars, with the SB-containing medium showing higher consumption of reducing sugars. Next, a Plackett&Burman 12 design was employed with 4 central points and 7 independent variables: LR:SB ratio, temperature (T, oC), cupuaçu pulp (CP, % w/v), hydro- soluble extract of cupuaçu almond (HECA, % v/v), rice flour (RF, % w/v), commercial sucrose (CS, % w/v), and pH. The responses analyzed were TCGC (final count (FC) - initial count (IC)), pH, total acidity, RS, TS, and exopolysaccharides (EPS) at initial time (0h) and final times (8h and 12h). The variables that exerted statistically significant and positive effects on TCGC were temperature and HECA content. Assay 7, with only SB (37oC; 20% HECA), presented the highest TCGC with an increase of 2.81 Log CFU/mL in 8h. The assays at the central points with a 50:50 LR:SB ratio obtained the best results in EPS production, reaching around 2.0 g/L. Assay 5, with only LR (37oC; 20% HECA; 12h), and the central points with a 50:50 LR:SB ratio showed the highest consumption of TS, while for RS, assays 6 (37oC, CS=8%, 12h) and the central point had the highest values. Assay 5 exhibited the highest pH variation after 12h of fermentation (from 5.19 to 4.46) and the highest lactic acid production after 8h of fermentation (419.88%). Regarding post-probiotic functionality, it was observed that the survival of microorganisms after the intestinal phase averaged 31%, losing up to 4 Log CFU/mL and resulting in counts below 3 Log CFU/mL. These results indicate that the cell count was not sufficient for effective colonization of the large intestine, and it is recommended to maintain the cell count at least at 6 Log CFU/mL. In conclusion, SB and LR microorganisms were able to ferment the cupuaçu pulp and almond extract-based medium, resulting in a non-conventional option for the functional beverage market. It is recommended to ferment with individual microorganisms, as the mixture did not contribute to increased cell growth.